2020
DOI: 10.1371/journal.pone.0241282
|View full text |Cite
|
Sign up to set email alerts
|

Demographic history and selection at HLA loci in Native Americans

Abstract: The American continent was the last to be occupied by modern humans, and native populations bear the marks of recent expansions, bottlenecks, natural selection, and population substructure. Here we investigate how this demographic history has shaped genetic variation at the strongly selected HLA loci. In order to disentangle the relative contributions of selection and demography process, we assembled a dataset with genome-wide microsatellites and HLA-A , -B , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
4
15
0
Order By: Relevance
“…1B ). The finding that the AMR participants have a larger number of HLA alleles is consistent with other studies and reference panels which showed that native American populations have a high number of HLA alleles absent in other populations 2022 . As expected, most of the HLA alleles were rare (minor allele frequency [MAF] < 1%) in all ancestries, with 166 out of 5,295 alleles with MAF > 1% in the EUR cohort and 209 out of 1,304 alleles with MAF > 1% in the AMR cohort (supplementary figure SF2 ).…”
Section: Resultssupporting
confidence: 91%
“…1B ). The finding that the AMR participants have a larger number of HLA alleles is consistent with other studies and reference panels which showed that native American populations have a high number of HLA alleles absent in other populations 2022 . As expected, most of the HLA alleles were rare (minor allele frequency [MAF] < 1%) in all ancestries, with 166 out of 5,295 alleles with MAF > 1% in the EUR cohort and 209 out of 1,304 alleles with MAF > 1% in the AMR cohort (supplementary figure SF2 ).…”
Section: Resultssupporting
confidence: 91%
“…The dataset of HLA I alleles used for epitope prediction included: (1) HLA-A, HLA-B and HLA-C alleles that presented the top ten highest frequencies in the Colombian general population (Dataset: Colombia-Bogotá). As well as, (2) the HLA-A, HLA-B and HLA-C alleles that exhibited the highest frequency for each of the eleven Colombian Amerindian groups with HLA I frequencies reported in the AFND [28], which coincided with the results of the literature search [29][30][31]. These Amerindian groups were: Arhuaco, Embera, Inga, Kogi, Chimila Norte, Wiwa Norte, Waunana, Wayyu, Zenú, Ticuna Arara, and Ticuna Tarapaca.…”
Section: Hlas Selection For Epitope Predictionsupporting
confidence: 67%
“…Of note, these populations also show the highest number of private HLA-DRB1 alleles ( Gonzalez-Galarza et al, 2021 ), which account for a high proportion of their allele pools ( Meyer et al, 2006 ) and are thought to be the result of selective forces acting in a context of severely reduced HLA diversity ( Titus-Trachtenberg et al, 1994 ; Erlich et al, 1997 ; Hollenbach et al, 2001 ). In fact, a mixture of long-term balancing selection and a combination of episodes of more recent positive and balancing selection has been associated with simultaneously increasing intra-population diversity and inter-population differentiation in Native Americans ( Single et al, 2020 ; Nunes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%